Zhang Zhan’s thought on Xujing in the commentary of Liezi - Na, Zhang; Mohd Syahmir Alias, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Zhāng Zhàn lived during the Eastern Jin period. Commentary on Lièzǐ is Zhāng Zhàn’s attempt to integrate and synthesize the previous achievements in metaphysical studies, merging Confucianism and Daoism while drawing from Buddhist viewpoints. This work represents a theoretical summary of metaphysical themes. This article aims to explore Zhāng Zhàn’s concept of xūjìng (emptiness and tranquility), examining its manifestations in cosmology, ontology, and the philosophy of life. This study adopts a qualitative research approach utilizing NVivo qualitative data analysis software, electronic databases, and a thorough analysis of the textual references to xūjìng in the Commentary on Lièzǐ. Three points were discovered: firstly, Zhāng Zhàn’s concept of tàixū (supreme emptiness) in cosmology; secondly, his doctrine manifests in ontology as zhìxū (ultimate emptiness); thirdly, his doctrine manifests in the philosophy of life as xūjìng zìrán (emptiness, tranquility, and naturalness). He asserts that people should not violate the laws of nature and should spiritually transcend the mindset of dealing with everything in the real world. According to Zhāng Zhàn, only by doing so can individuals align with the Dào, surpass the mundane, and attain the state of carefree detachment. This study provides a deeper significance of Zhāng Zhàn’s concept of emptiness and tranquility from the perspectives of ontology, cosmology, and philosophy of life. According to Zhāng Zhàn, emptiness is infinite, and only by embodying non-being and making emptiness the essence can one harmonize with the Dào, achieve liberation, and attain a spiritual state of unity with the universe.